FAKOR-FAKTOR YANG MEMPENGARUHI KINERJA PERBANKAN YANG TERDAFTAR DI BEI - Khusnul Faizin, 12.05.52.0126; Nurhayati, Ida (Students' Journal of Accounting and Banking, 2017)
This study aims to determine the effect of the Capital Adequacy Ratio, Loan to Deposit Ratio, Operating Expenses, Non-Performing Loans, Loan to Asset Ratio, Against ROA. The population in this study is a banking company from 2012 to 2015. The sample in this study were taken by purposive sampling method. Data were analyzed using skewness-kurtosis normality test, test multiple linear regression analysis. The test results In CAR variable statistically significant negative effect on ROA, On LDR variable statistically significant negative effect on ROA, In variable BOPO statistically significant negative effect on ROA, On NPL statistically significant positive effect on ROA, At variables LAR in statistically significant positive effect on ROA.Keywords: CAR, LDR, ROA, NPL, LAR, ROA